2014
DOI: 10.4038/kjm.v2i1.6545
|View full text |Cite
|
Sign up to set email alerts
|

Women Managers and Their Personal Barriers for Upward Mobility in Private and Public Sectors

Abstract: Women's participation in the paid workforce is one of the most significant social changes of the last century. Therefore, significant progress has been achieved by women with their increase movements into the occupations and the proportion of women in management of different levels of the organizations has increased. However, towards the end of year 2012 the proportion of women in decision making is very low and still there are only around 20 per cent women are represent the managerial positions. Qualitative c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…A case study was conducted in Sri Lanka to find the perceived personal barriers that inhibit to the career development of women. The study found that there was a lack of organizational support and extensive tasks and working load (Jayatilake et al 2014;Britton and M 2010). Increased teaching workload leads to low research productivity and women academics are more burdened at work compared to men (Peetz et al 2014a(Peetz et al , 2014b.…”
Section: Findings and Resultsmentioning
confidence: 99%
“…A case study was conducted in Sri Lanka to find the perceived personal barriers that inhibit to the career development of women. The study found that there was a lack of organizational support and extensive tasks and working load (Jayatilake et al 2014;Britton and M 2010). Increased teaching workload leads to low research productivity and women academics are more burdened at work compared to men (Peetz et al 2014a(Peetz et al , 2014b.…”
Section: Findings and Resultsmentioning
confidence: 99%
“…Leadership positions demand more time and commitment, which women feel they can ill afford and thus they settle for lesser roles and buy family peace instead. Many times, women also opt out of leadership responsibility to maintain a work–life balance (Jayatilake et al, 2014). As a leadership position is looked at as a 24/7 type of role, many working women prefer to opt out as it leaves them with unmet important needs.…”
Section: Discussionmentioning
confidence: 99%
“…This provides a significant contribution to the literature on impediments for women at board room level with a holistic perspective, which has received limited academic attention over the years (Cohen et al, 2020;Reddy & Jadhav, 2019;Terjesen et al, 2009;Terjesen & Singh, 2008). Addressing the observation of Jayatilake et al (2014) that existing literature could not establish determinants of female career advancement with a complete view, we demonstrate in this study that multifaceted variables holistically impact women's progression towards board room positions. This understanding implies that initiatives such as introducing gender quotas at the board level will not be able to achieve the desired results (Ferreira, 2015).…”
Section: Implications Of the Studymentioning
confidence: 75%
“…The gender divide in the organizational hierarchy is highly noticeable with more male employees at the top. While most of the statistics provide positive rays of hope about the country's ambitious efforts to enhance women's wellbeing, there is limited academic attention detailing the women's participation at the boardroom level (Jayatilake et al, 2014;Uduwella & Jayatilaka, 2019). Due to these reasons, Sri Lanka can be considered a viable research site to explore the obstacles that hinder women's career progression in the finance sector.…”
Section: Sri Lanka As the Research Sitementioning
confidence: 99%